Osteosynthesis or arthroplasty of fractures near the knee joint in geriatric patients – a clinical-economical comparison - Pasurka, Mario; Krinner, Sebastian; Gelse, Kolja (Zeitschrift für Orthopädie und Unfallchirurgie, 2020)
BACKGROUND: The treatment of fractures of the tibial plateau or distal femur often represents a severe problem in geriatric patients. In particular, complex fracture types and concomitant severe osteoporosis are confronted with inferior results following internal fixation. Therefore, primary arthroplasty is increasingly propagated for such particular cases. PATIENTS, MATERIALS AND METHODS: In 16 patients suffering from fractures of the distal femur or tibial plateau were treated either by internal fixation (n = 8) or primary arthroplasty (n = 8). The outcome of each case was retrospectively analysed according to clinical and economic criteria. RESULTS: In the investigated geriatric patients, primary arthroplasty was significantly superior to internal fixation regarding mobilisation and range of motion without being inferior in cost-effectiveness. CONCLUSION: Compared to internal fixation, primary arthroplasty represents an efficient and cost-effective therapeutical option for the treatment of complex fractures of the distal femur or tibial plateau of the elderly patient.
CRIS-Team Scopus Importer:2020-06-30